Mouse Double Minute 2 Homolog-Mediated Ubiquitination Facilitates Forkhead Box P3 Stability and Positively Modulates Human Regulatory T Cell Function - Wang, Aiting; Yang, Mengdi; Liang, Rui; Zhu, Fangming; Zhu, Fuxiang; Liu, Xinnan; Han, Yichao; Lin, Ruirong; Wang, Xiaoxia; Li, Dan; Li, Hecheng; Yuan, Xiaojun; et al. (Frontiers in Immunology, 2020)
Regulatory T cells (Treg cells) are essential for maintaining immune tolerance, and the dysfunction of Treg cells may cause autoimmune diseases and tumors. Forkhead box P3 (FOXP3) is the key transcription factor controlling Treg cell development and suppressive function. Mouse double minute 2 homolog (MDM2), an E3 ubiquitin ligase, has been identified as an oncoprotein that mediates the ubiquitination and degradation of tumor suppressor p53; however, whether it has functions in Treg cells remains unknown. Here, we demonstrate that MDM2 positively regulates human Treg cell suppressive function via its mediated ubiquitination and stabilization of FOXP3. Knockdown of MDM2 with shRNA in human primary Treg cells leads to the impaired ability of FOXP3 to regulate the expression levels of downstream genes and the attenuated suppressive capacity of Treg cells, due to FOXP3 instability. Consistently, MDM2 overexpression in human Treg cells enhances FOXP3 stability and Treg cell suppressive capacity. Mechanistically, MDM2 interacts with FOXP3, and mainly mediates monoubiquitination and polyubiquitination of FOXP3, thus stabilizing the protein level of FOXP3. We have also found lysine residues in FOXP3 required for MDM2-mediated ubiquitination. In addition, TCR/CD28 signaling upregulates the expression level of MDM2 and its mediated FOXP3 ubiquitination in human Treg cells. Therefore, our findings reveal that MDM2 in Treg cells could be a potential therapeutic target for treating autoimmune diseases and tumors.